The Effects of Wheat Germ Supplementation on Anthropometric, Biochemical, and Stool Measures in Overweight Adults. (29th May 2020) - Dotimas, Levin; Ojo, Babajide; Alake, Sanmi; Kaur, Amritpal; Dixon, Madison; Emerson, Sam; Chowanadisai, Winyoo; Lucas, Edralin
Abstract: Objectives: This study investigated the effects of a 4-week wheat germ supplementation on anthropometric, biochemical, and stool measures in overweight adults. Methods: Forty overweight (body mass index = 25.0–30 kg/m 2 ) adults (18–45 years old) were recruited to participate in this randomized controlled study. After initial screening, participants were asked to consume energy balls containing either cornmeal (control) or 30 g of wheat germ (WG) daily for 4 weeks. The energy balls were isocaloric and provided an additional 225 kcal/day. Participants were asked to otherwise maintain their normal diet and physical activity. Anthropometric and metabolic parameters, as well as dietary (3-day food record), medical history, physical activity (Yale Physical Activity Survey) and stool measures (Bristol Stool Chart and the Cleveland Clinic Constipation Scoring System) were assessed at baseline and at the end of the 4-week supplementation period. Results: Thirty-nine participants completed the 4-week supplementation ( n = 20 and 19 for the WG and control group, respectively). There were no significant differences in anthropometrics, metabolic parameters (i.e., lipid panel, glucose, and HbA1c) or stool measures between the control and WG groups at baseline or at the end of supplementation. However, when comparing change from baseline, significant differences in % body fat, HbA1c, and constipation score were observed between the two groups. Individuals who received the WG supplement exhibited a greater increase in % body fat (0.68 ± 0.28% vs. 0.40 ± 0.36%, P = 0.02) and a greater decrease in HbA1c (−0.095 ± 0.05% vs. −0.039 ± 0.04%, P = 0.04). On the other hand, the control group (−1.00 ± 0.57) perceived a more significant improvement ( P = 0.01) in their constipation score compared to WG (−0.85 ± 0.42). Conclusions: Similar to our findings in animals, this study demonstrates that daily supplementation with 30 g of WG may be beneficial in glucose homeostasis as indicated by improvement in HbA1C, despite increasing % body fat. Whether the effects of WG on HbA1C will be observed at longer supplementation duration or in other populations such as obese individuals or pre-diabetics needs to be investigated in future studies. Funding Sources: United States Department of Agriculture.